Nursery Rhymes - Neave, Rosie; Wood, Hannah; Harmer, Sharon; Feit, Luciana; The Pope Twins (Essex, United Kingdom : Miles Kelly Publishing Ltd., 2014)
This delightful compendium presents themed nursery rhymes across large format pages of full-bled artwork scenes. Every page showcases beautiful illustrations packed with charm and detail. All the best-known rhymes that children love have been included, and the book has been split into four sections: Singing Rhymes, Number Rhymes, Playing Rhymes and Bedtime Rhymes.
Singing Rhymes -- Playing Rhymes -- Number Rhymes -- Bedtime Rhymes.
Keywords: Nursery rhymes, English; Textured books; Board books